Sustainable preservation of dried fish using hybridized plant extracts: HPLC-based quantification of aflatoxins and vitamins, and assessment of broad-spectrum antimicrobial efficacy - Manal Almughamisi; Hilary Uguru; Dennis Adaigho; Ola A. Abu Ali; Sarah Alharthi; Rokayya Sami; Roqayah H. Kadi; Afnan M. Alnajeebi; Amera N. Alqahtani; Shatha H. Alaoufi; Moayad M. Khashoqji; Alaa H. Felemban; et al. (PLoS ONE, 2026)
This research aimed to preserve the nutritional qualities of fish flesh during prolonged storage, by utilizing bioactive compounds derived from plant extracts and oils. Fish flesh (tissues) was treated with lime, ginger, turmeric, banana peel extracts, and oils – including their hybridized forms. The dried fish samples nutritional quality, and microbial population were measured using established protocols. Results obtained revealed that the treatments played significant roles, in enriching the fish nutritional quality and also inhibiting microbial growth during storage. It was observed that the treatments played a substantial role, in the preservation of the nutritional integrity of dried fish (mostly the proteins and vitamins), during the extended storage duration. Also, most of the hybridized treatments displayed synergistic mechanistic effects, which resulted in enhanced antimicrobial and nutrient retention actions. Conspicuously, the lime extract played a critical role in potentiating the treatments antimicrobial efficacy (T8 to T13). The results revealed that the control sample had higher bacterial and fungal growth at week 8; whereas, treatments T8 to T13 displayed superior antimicrobial activities. Notably, T8 sample exhibited the best antimicrobial action, recording the lowest counts – Staphylococcus spp. (52 CFU/g), Salmonella spp. (14 CFU/g), Bacillus spp. (3 CFU/g), Listeria spp. (5 CFU/g), Aspergillus spp. (black mold) (11 CFU/g), Penicillium spp. (7 CFU/g), Aspergillus spp. (flavus group) (37 CFU/g), and Rhizopus spp. (14 CFU/g). It was also observed that, most of the combined treatments were able to retard aflatoxin formation in the fish tissues, to a safer level of lower than 4 µg/kg. This study’s findings have revealed the sustainability aspects, predominantly the conversion of agricultural products into value-added bio-additives in food processing and preservation.